Constraints on the Use of a Learning Management System in a Blended Learning Environment - Vilela-Malabanan, Cenie M.; Echavez, Nancy Q. (International Journal on Open and Distance e-Learning, 2018)
This research investigated the blended learning environment constraints when academics use a learning management system (LMS). With the prevalent use of educational technologies including the LMS, a mix of traditional face-to-face and web-based technologies became an alternative mode of instructional delivery in higher education. However, despite of the reported benefits in many studies about the use of LMS, the uptake of using the system was not maximized by students and by academics. The problem this research sought to answer was: what were the constraints encountered by the academics in a blended learning environment? This investigation was conducted in a state university based in Mindanao, Philippines. Thirty-three academicsfrom different disciplines and professorial levels participated in this study. The LMS used in this university was Moodle and records of computer logs indicated that only 30% of academics used the LMS. Two major processes were carried out in this investigation. Firstly, a qualitative approach which employed a onehour, one-on-one in-depth interview with each participant was conducted. Data were then transcribed and coded in three stages: open, axial, and selective coding. Qualitative data were analyzed using a grounded theory approach. Secondly, a quantitative approach, using descriptive statistics was used in the analysis of the participants’ computer logs which were gathered and processed using a simple data mining procedure. The findings in this study suggested that academics had been experiencing difficulties in delivering courses in a technology-enhanced learning environment particularly with the use of LMS. Difficulties in time management, curriculum level, students' access, and economic viability were found to cause the constraints.